2005
DOI: 10.1080/00207390500064650
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent brief depression revisited

Abstract: Recurrent Brief Depressive Disorder (RBD) is a well-defined and prevalent mood disorder with an increased risk of suicidal behavior and significant clinical impairment in the community and general practice. Occurring at least monthly with depressive episodes lasting only a few days defines recurrent Brief Depressive Disorder. The lifetime co-occurrence of both RBD and Major Depressive Disorder (MDD), called Combined Depression (CD), substantially increases the risk for attempted suicide, even more than that kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 38 publications
(57 reference statements)
2
15
0
Order By: Relevance
“…A replicated association has been found between amygdala reactivity to emotional stimuli and a polymorphism in the serotonin transporter gene (Hariri et al, 2002Pezawas et al, 2005), and other genes in the serotonergic pathway also seem to influence amygdala reactivity (Brown et al, 2005;Buckholtz et al, 2007;Dannlowski et al, 2007;Iidaka et al, 2005). tioning.…”
Section: Introductionmentioning
confidence: 96%
“…A replicated association has been found between amygdala reactivity to emotional stimuli and a polymorphism in the serotonin transporter gene (Hariri et al, 2002Pezawas et al, 2005), and other genes in the serotonergic pathway also seem to influence amygdala reactivity (Brown et al, 2005;Buckholtz et al, 2007;Dannlowski et al, 2007;Iidaka et al, 2005). tioning.…”
Section: Introductionmentioning
confidence: 96%
“…Hamilton Depression Rating Scale) when used in the conventional weekly manner with fixed follow-up intervals may not be optimal as they only capture symptoms present within the week before, and may not accurately portray the variable course of RBD that can occur even within a single week. Other factors include the lack of study designs with appropriate statistical sensitivity and longer periods of observations (Pezawas et al, 2005). Despite the recognition of RBD in the DSM-IV, the level of acceptance for this diagnosis in North America appears to be limited.…”
Section: Discussionmentioning
confidence: 94%
“…Contradictory results have been attributed to differences in the design, statistical analysis and types of subject included (e.g. comorbidity) (Stamenkovic et al, 2001;Pezawas et al, 2005). Corominas et al (1998) have proposed that agents which help prevent repeated depressive episodes in bipolar disorder might also be useful in RBD.…”
Section: Among Othersmentioning
confidence: 96%
“…There is some evidence that treating more depressed patients with AD might prevent suicide [3]. However, some concerns have been raised over the fact that AD use, mainly Selective Serotonin Reuptake Inhibitors (SSRI) may increase the risk of suicide [4]. Ecological studies showed some evidence that more widespread AD use corresponds to a decrease in suicide rates [1], although this finding is disputed [5].…”
Section: Introductionmentioning
confidence: 99%